PENGEMBANGAN STRATEGI USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA PEKANBARU - Muhammad Aidil Fitra; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the development strategy and to determine the factors that hamper the MSME development strategy in the city of Pekanbaru. This research is a study that uses a qualitative methodology. This research is descriptive in nature, describing the truth correctly about the MSME development strategy in the city of Pekanbaru. Qualitative research aims to reveal certain social situations by describing true reality. The results of this study are the strategies for developing MSMEs in the city of Pekanbaru that are implemented by the Pekanbaru City Cooperative Office of MSME are organizational strategies, program strategies and institutional strategies. In implementing this organizational strategy the Pekanbaru City Cooperative Office of MSME has not yet maximized the formulation of new strategic initiatives, the formulation of strategic initiatives undertaken tends to be almost the same as in previous periods. In the implementation of this program strategy the Pekanbaru City Cooperative Office of MSME has not been able to be implemented as planned due to lack of functional technical ability and delays in disbursing funds. In the implementation of this institutional strategy, the Pekanbaru City Cooperatives MSME Office's lack of ability to implement the strategic initiatives that have been formulated. Factors that hamper the MSME development strategy in Pekanbaru are internal factors consisting of functional technical capabilities, workloads that are not standardized, and inadequate infrastructure. Also external factors consisting of the threat of the influence of globalization, and disbursement of funds that are not in accordance with the specified time.Keywords: Development, Strategy, MSME